An Empirical investigation of the value of High and Low price data to Modern Portfolio Theory - MacDevette, Ciaran (Division of Actuarial Science, 2014)
It is common practice to use the return series from closing prices in order to estimate the values of variables to be used in Modern Portfolio Theory (MPT). In fact the closing price series is generally what is referred to when price data or a financial time series is mentioned. We know this series to be made up of discrete points recorded as the last traded price on a specific day. But we also know this gives no indication of where the price has moved during the day. It is also widely believed that the price breaking through a certain level can be an indication of future movements. The highs and the lows, regardless of what one may believe they represent exactly, do, together with the closing prices, give a more complete view of the behaviour of a moving price. Yet they are for the most part left unused. It is known that the series of highs and lows are published and are widely available, at least as available as closing prices. The question that needs to be answered is: are the highs and lows valuable enough to warrant their use in MPT, and if so, what would this entail? It will be attempted, through an empirical study, to determine whether or not it is worthwhile to incorporate the highs and lows into the existing framework of MPT, and how this might be accomplished. It must be discovered more clearly whether there is extra information in the highs and lows that is not in the closings. The high and low series must also be used in core procedures like the calculation of the efficient frontier or the determination of actual portfolios in order to see if there is an appreciable difference to just using closings. This should give is an indication of how one might use the highs and lows in MPT if they are indeed deemed valuable.